A Weakening Transatlantic Relationship? Redefining the EU–US Security and Defence Cooperation - Bjørn Olav Knutsen (Politics and Governance, 2022)
The aim of this article is to discuss how a weakening transatlantic relationship influences European defence cooperation and integration. It also asks how these observed patterns of weakening EU–US relations can be explained and what the consequences might be for the EU’s efforts to build a stronger and more coherent security and defence policy. Building upon a “comprehensive neo-functionalist” approach first coined by the Norwegian scholar Martin Sæter, European security and defence policy should be seen as part of an externalisation of EU integration as a response to weakening transatlantic relations. The debate on European “strategic autonomy,” the Strategic Compass, and the European “defence package” should therefore be considered as part of such an externalisation process of actively influencing and reshaping the transatlantic relationship. When analysing European security and defence, the article also shows that it is misleading to regard European integration as something to be subordinated to NATO. Nevertheless, a European security deficit does exist due to differing perspectives among member states on how the EU process should relate to NATO. The article, therefore, concludes that strategic autonomy can only be developed with close EU–NATO cooperation. Furthermore, a more multipolar world order where the EU no longer can rely upon a transatlantic security community to the same extent as before challenges the EU’s role as a defender of multilateralism and poses new challenges to the EU’s common foreign and security policy.